VD_FINDINFO Jug / 2018 / 89 vom 3. November 2017 - VD Tribunal cantonal (2017)
CONSTATATION DES FAITS, DOMMAGES À LA PROPRIÉTÉDROIT PÉNAL, INJURE | 144 CP, 177 CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH)